2004
DOI: 10.1370/afm.220
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reports of Preventable Problems and Harms in Primary Health Care

Abstract: BACKGROUND Despite recent attention given to medical errors, little is known about the kinds and importance of medical errors in primary care. The principal aims of this study were to develop patient-focused typologies of medical errors and harms in primary care settings and to discern which medical errors and harms seem to be the most important.METHODS Thirty-eight in-depth anonymous interviews of adults from rural, suburban, and urban locales in Virginia and Ohio were conducted to solicit stories of preventa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
166
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(187 citation statements)
references
References 19 publications
(14 reference statements)
10
166
1
7
Order By: Relevance
“…Physicians with no-claim seemed to conduct longer visits, educate patients more, check understanding more and use more humour during the visit than physicians with claims [9]. A study by Kuzel [10] showed that negative outcomes in the clinician-patient relationship, dominated by stories of disrespect or insensitivity, were reported as more common than technical errors in diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians with no-claim seemed to conduct longer visits, educate patients more, check understanding more and use more humour during the visit than physicians with claims [9]. A study by Kuzel [10] showed that negative outcomes in the clinician-patient relationship, dominated by stories of disrespect or insensitivity, were reported as more common than technical errors in diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians with no-claim seemed to conduct longer visits, educate patients more, check understanding more and use more humour during the visit than physicians with claims [9]. A study by Kuzel [10] showed that negative outcomes in the clinician-patient relationship, dominated by stories of disrespect or insensitivity, were reported as more common than technical errors in diagnosis and treatment.The Institute for Healthcare Improvement (IHI) emphasizes that the health care system needs to be more patient-centred and to involve the patients and families in the design of care. Patient-centred care requires respect for patients' values and expressed needs, information and communication, coordination of care, involvement of family, 4 and concordance between the patient and health professionals [11].…”
mentioning
confidence: 99%
“…4 See Hibbard, Peters, Slovic, and Tusler M., 2005;Blendon, DesRoches, Brodie, et al, 2002;Marella, Finley, Thomas, and Clarke, 2007;Schwappach, 2010;Schwappach and Wernli, 2010; The Kaiser Family Foundation/Agency for Healthcare Research and Quality, 2008;Waterman, Gallagher, Garbutt, Waterman, Fraser, and Burroughs, 2006. 5 See Basch, Artz, Dulko, et al, 2005;Kuzel, Woolf, Gilchrist, et al, 2004;Weingart, Gandhi, Seger, et al, 2005;Weingart, Pagovich, Sand, et al, 2005;Weingart, Pagovich, Sands, et al, 2006;Weingart, Price, Duncombe, et al, 2007;Zhu, Stuver, Epstein, Schneider, Weissman, and Weingart, 2011. 6 See Agoritsas, Bovier, and Perneger, 2005;Blenkinsopp, Wilkie, Wang, and Routledge, 2007;Friedman, Provan, Moore, and Hanneman, 2008. These researchers succeeded in eliciting patient safety reports through patient interviews; however, patient reports frequently require recoding or classification to enable the extraction of the key content, resolve discrepancies or inconsistencies, and assess the attribution of symptoms or complications to care rather than to the natural history of disease.…”
Section: Value Of Patient Reportingmentioning
confidence: 99%
“…Two tasks help develop mistake disclosure strategies: 1) the context of disclosure delivery and 2) the content of mistake messages, sequencing, and apology. 5,[33][34][35] …”
Section: Information Seekingmentioning
confidence: 99%